Extracranial carotid artery atherosclerotic plaque and APOE polymorphisms: a systematic review and meta-analysis - Culleton, Sinéad; Niu, Mary; Alexander, Matthew; McNally, J. Scott; Yuan, Chun; Parker, Dennis; Baradaran, Hediyeh (Frontiers in Cardiovascular Medicine, 2023)
Introduction Carotid atherosclerotic plaque is an important independent risk factor for stroke. Apolipoprotein E (APOE) influences cholesterol levels and certain isoforms are associated with increased carotid atherosclerosis, though the exact association between APOE and carotid plaque is uncertain. The study aimed to evaluate the association between APOE and carotid plaque. Methods A systematic review was performed to retrieve all studies which examined the association between carotid plaque and APOE. This study was conducted in accordance with the PRISMA guidelines. Independent readers extracted the relevant data from each study including the type of imaging assessment, plaque definition, frequency of APOE E4 carrier status and type of genotyping. Meta-analyses with an assessment of study heterogeneity and publication bias were performed. Results were presented in a forest plot and summarized using a random-effects model. Results After screening 838 studies, 17 studies were included for systematic review. A meta-analysis of 5 published studies showed a significant association between ε4 homozygosity and carotid plaque [odds ratio (OR), 1.53; 95% CI, 1.16, 2.02; p = .003]. Additionally, there was a significant association between patients possessing at least one ε4 allele, heterozygotes or homozygotes, and carotid plaque (OR, 1.25; 95% CI, 1.03, 1.52; p = .03). Lastly, there was no association between ε4 heterozygosity and carotid plaque (OR, 1.08; 95% CI, 0.93, 1.26; p = .30). Conclusion APOE ε4 allele is significantly associated with extracranial carotid atherosclerotic plaque, especially for homozygous individuals.